Bibliometric mapping of research developments on the topic of Efforts to Accelerate Stunting Reduction on ProQuest using VOSviewer - Kurniawan, Fajar; ., Nurwati; ., Jafriati; ., Patwayati (International Journal of Membrane Science and Technology, 2023)
Research methods using VOSviewer application – Visualizing the scientific landscape (bibliometry) quantitative approach used to analyze and evaluate scientific papers that have been published in a particular field of knowledge. In conducting a literature review using a bibliometric approach, researchers collect and analyze various types of scientific publications such as journals, conference articles, and theses related to the research topic being investigated. The results of the study are known to be assumed that. The results of this study provide a strong foundation for assessing the success of stunting reduction efforts, identifying possible collaborations, and formulating future research directions related to the success of national priority programs that include accelerating the reduction in stunting incidence. The need for future researchers to conduct similar research by modifying specifically by adding mediating variables related to organizational behavior where public health efforts which are health programs at first-level health facilities with good governance can certainly contribute to the reduction of stunting, but the rapid slow decline in the incidence of stanting depends on the behavior in the organization, namely the commitment of officers health and motivation work in health workers in such first-level service facilities. With the hope that further research can develop research by examining public health efforts towards the success of national priority programs by increasing mediation, work commitment, and work motivation.